Kisameet Clay Isolated from the Central Coast of British Columbia, Canada, Demonstrates Broad-Spectrum Antimicrobial Activity - Zhanel, George G. (mBio, 2016)
Clay minerals are naturally occurring layered phyllosilicates which consist of fine particles and possess antimicrobial activity. In a recent article, Behroozian et al. obtained Kisameet clay (KC) from Kisameet, from the central coast of British Columbia, Canada, northwest of Vancouver and assessed its antimicrobial activity versus 16 selected ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp.) possessing a variety of different resistance profiles [S. Behroozian, S. L. Svensson, and J. Davies, mBio 7(1):e01842-15, 2016, http://dx.doi.org/10.1128/mBio.01842-15]. KC demonstrated complete bacterial eradication of Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Staphylococcus aureus within 24 h. For Enterobacter spp., the organisms were eradicated with 1% KC within 5 h, while for Enterococcus faecium, it took 48 h to kill all organisms. Although many questions need to be answered, these exciting findings highlight the importance of testing natural substances/products from around the globe to assess whether they possess antimicrobial activity and potential for usage as topical, oral, or systemic agents for the treatment of multidrug-resistant pathogens.